The Prohibition\'s Sanction of Abuse of Rights in Iranian and French Civil Proceedings - mohammad bafahm; azizolah fahimi; Mahdi Hasanzadeh (پژوهش های حقوق تطبیقی, 2023)
Litigants have several rights in civil proceedings; these rights may be abused. In this regard, according to Article 40 of the Iran's Constitution and other principles (including the role of prohibiting the abuse of rights as one of the legal principles, paying attention to the purpose of civil proceedings, public order, and the role of ethics in law), the abuse of rights in civil proceedings is also prohibited. Prohibition of abuse of rights, like other legal rules, requires a sanction; according to this, it is necessary to identify the sanction of this legal principle, and the present research has been presented for this purpose. The results of this article indicate that the prohibition's sanction of the abuse of rights in civil proceedings is divided into two categories: general sanction (including "non-ordering of the effect on the abusive act" and "compensation") and special sanction (including "civil fine" and "criminal responsibility"). Each of these sanctions have specific nature, conditions and rules that are explained in this research.